Privatized Futures, Climate Control, and Resistance in Recent Scottish Dystopian Fiction - Peter Clandfield (Sillages Critiques)
This article addresses Scottish dystopian novels that move past ideas of the British state as Big Brother to envision future Scotlands encountering global problems of climate change and its exploitation by neoliberal regimes. After discussing Alasdair Gray’s 1982, Janine (1984) as an influential confrontation with the increasingly toxic military-industrial state of 1980s Britain, the essay interprets Matthew Fitt’s But n Ben A-Go-Go (2000), John Aberdein’s Strip the Willow (2009), and the multiple-author graphic novel IDP: 2043 (2014), edited by Denise Mina, as what Umberto Eco calls “novels of anticipation,” or warnings of the undesirable eventualities that present tendencies may bring about. The essay shows how these novels also anticipate recent critical perspectives on climate change and dystopia, particularly Amitav Ghosh’s call (2016) for fiction that confronts the potentially intractable effects of global weather events, and Tom Moylan’s advocacy (2020) of works that resist presenting dystopian spectacles for passive consumption and instead call upon readers for active, constructive interpretation.